National Institute Pulmonary Hypertension Registry (NIPHeR): Insights from the first pulmonary hypertension registry of Pakistan - Abubaker, Jawed; Shaikh, Abdul Sattar; Hassan, Mujtaba; Ammar, Ali; Tauseef, Usman; Arif, Muhammad Sohaib (Journal of the Pakistan Medical Association, 2025)
Objective: To analyse the characteristics, management and outcomes of patients with pulmonary hypertension from a dedicated registry. Method: The retrospective study was conducted at the Pulmonary Hypertension Clinic of the National Institute of Cardiovascular Disease (NICVD), Karachi from November 2021 to July 2023, and comprised data of patients above eighteen years diagnosed with pulmonary hypertension. Data was retrieved from the National Institute Pulmonary Hypertension Registry (NIPHeR), and was categorised as per the 6th World Symposium on Pulmonary Hypertension 2018 classification into groups 1-5. Patient data was collected using a Proforma. Data was analysed using SPSS 27. Results: Of the 145 patients with mean age 43.10±14.71 years, 92(63%) were females. Group 4 had the most number of patients 50 (34.5%). Dyspnoea and fatigue were the most common complaints, lasting a mean duration of 22.71±29.11 months. The majority 94 (65%) of patients had New York Heart Association Functional Class III or IV, but within 6 months of treatment, the number went down to 72(49.6%). Mortality was reported in 9 (6.2%) cases, and it was significantly associated with Group 4 (p<0.05). Factors significantly associated with increased mortality were Group 4 PH (Pulmonary hypertension associated with pulmonary embolism), an electrocardiographic evidence of right ventricle hypertrophy (RVH) along with severe or persistent right ventricle dysfunction, and use of Endothelin receptor antagonists (ERA) as monotherapy, while there use in combination with phosphodiesterase 5 (PDE5) inhibitors was associated with decreased mortality (P<0.05) Conclusion: The importance of early diagnosis and appropriate management of pulmonary hypertension cannot be overemphasized. The National Institute Pulmonary Hypertension Registry could serve as a vital tool for understanding regional trends and guiding future clinical practice and research in pulmonary hypertension. Key Words: Pulmonary hypertension, Registry, Pulmonary artery, Echocardiography, Vasodilator agents, Mortality.